Thyroid Function in Preterm/Low Birth Weight Infants: Impact on Diagnosis and Management of Thyroid Dysfunction - LaFranchi, Stephen H. (Frontiers in Endocrinology, 2021)
Fetal thyroid hormone production begins in the second trimester, with fetal serum T4 levels gradually rising to term. Full maturation of the hypothalamic-pituitary-thyroid (HPT) feedback axis does not occur until term gestation. Following delivery, the TSH surge is reduced in preterm as compared to term babies. The postnatal increase in T4 is reduced in proportion to the degree of prematurity, representing both loss of the maternal contribution and immaturity of the HPT axis. Non-thyroidal illness syndrome (NTIS) and some drugs used to treat co-morbidities contribute to this “hypothyroxinemia of prematurity”. In addition, iodine, both deficiency and excess, have an impact on thyroid function in infants born preterm. In those newborn screening (NBS) programs that undertake serial testing to detect congenital hypothyroidism, there is a relatively high incidence of “delayed TSH elevation” in preterm/LBW neonates. On follow-up, the majority of these cases have transient hypothyroidism. Preterm/LBW infants have many clinical manifestations that might be ascribed to hypothyroidism. Is hypothyroxinemia of prematurity, with thyroid function tests compatible with either NTIS or central hypothyroidism, a physiologic or pathologic process? In particular, does hypothyroxinemia contribute to the neurodevelopmental impairment common to preterm infants? Results from multiple studies are mixed, with some randomized controlled trials in the most preterm infants born <28 weeks gestation appearing to show benefit. This review will summarize fetal and neonatal thyroid physiology, thyroid disorders specific to preterm/LBW infants and their impact on NBS for congenital hypothyroidism, examine treatment studies, and finish with comments on unresolved questions and areas of controversy.